Synthesis And Characterization Of Indium And Gallium Based Nanowires - Hisham, Asma Amira Badrol (Universiti Sains Malaysia, 2017)
In this work, formation of In- and Ga- based nanowires was studied using chemical vapor deposition (CVD) method. The starting materials were In, Ga and ammonia gas (NH3) with gold as catalyst for the growth of nanowire on sapphire substrates. The samples were characterized by scanning electron microscopy equipped with energy dispersive X-ray spectroscopy, transmission electron microscopy, X-ray diffractometer and Raman Spectroscopy. Influence of growth parameters involved in CVD growth nanowires on morphology and structural of In- and Ga- based nanowires is presented. Growth parameters such as growth temperature (600°C, 700°C, 800°C and 850°C), growth time (30 mins, 50 mins, 70 mins and 90 mins), deposition time of gold thin film (1 second, 2 seconds and 3 seconds), different gold structure coating (gold nanoparticles and gold thin films) and ratio of metal sources (30:70, 40:60, 50:50, 60:40 and 70:30), In to Ga effected the structural and morphological of the formed nanowires. It is found that suitable temperature and time to grow the nanowires was at 700°C for 30 minutes. With 3 seconds deposited gold thin film, the formed nanowires appeared to have a rounded tip and helical structure of nanowire coils around an axis with a good distribution growth on the substrate surface. It is also found that different amount of In and Ga have an effect on the length of the formed nanowires. Samples synthesized with a higher amount of In formed a longer nanowires and sample synthesized with a higher amount of Ga formed a shorter nanowires.